Systemic treatments for thymoma and thymic carcinoma: A systematic review. (December 2018) - Berghmans, Thierry; Durieux, Valérie; Holbrechts, Stéphane; Jungels, Christiane; Lafitte, Jean-Jacques; Meert, Anne-Pascale; Moretti, Luigi; Ocak, Sebahat; Roelandts, Martine; Girard, Nicolas
Highlights: Chemotherapy may be proposed for advanced stages or recurrent thymic tumours. Cisplatin-based regimens showed the most effectiveness. Adding anthracycline or etoposide to platinum demonstrated similar activity. Immunomodulatory agents, acting on the PD1 axis showed promising results. Abstract: Thymic tumours are rare diseases that for most of the cases are cured with surgery and eventually adjuvant radiotherapy. However, about 30% of patients present with advanced stage or relapsing tumours, which require administration of chemotherapy. While cisplatin-adriamycin-cyclophosphamide combination is regularly prescribed, other drugs have been assessed in the literature. Our aim is to evaluate the effectiveness (response rate) of systemic treatments, whatever the therapeutic line, including chemotherapy, targeted therapies and immunotherapies, in thymoma and thymic carcinoma, using the principles of evidence-based medicine. A systematic review was designed using the PICO system, by an experienced librarian and clinicians' experts in thoracic oncology, through the Ovid Medline system. Only phase II-IV trials and retrospective studies including at least 14 patients treated with the same regimen were considered. Articles were independently selected by at least two investigators. Fifty-five eligible articles were retrieved. Sixty% were dealing with platinum-based regimens, mainly cisplatin, and showed overall similar activity (mostly response rate above 50%) independently of the line of treatment or histological type (thymoma versus thymic carcinoma). Non-platinum based regimens included octreotide-prednisone and capecitabine-gemcitabine. Promising data of immunotherapy with antiPDL1 antibody (pembrolizumab) requires confirmation. Based on available data, the most popular and active regimens are cisplatin-anthracycline (CAP or ADOC) or cisplatin-etoposide combinations that should be recommended when considering first-line chemotherapy in thymoma or thymic carcinoma.